S100A4 Protects Myeloid-Derived Suppressor Cells from Intrinsic Apoptosis via TLR4–ERK1/2 Signaling - Li, Qingcui; Dai, Chengliang; Xue, Rui; Wang, Peigang; Chen, Lin; Han, Yijie; Erben, Ulrike; Qin, Zhihai (Frontiers in Immunology, 2018)
Myeloid-derived suppressor cells (MDSCs) often expand during cancer or chronic inflammation and dampen immune responses. However, mechanisms underlying their capacity to escape intrinsic apoptosis in the inflammatory environment are still largely unknown. In this study, we investigated this in mouse tumor models with MDSC accumulation. Spontaneous rejection of tumors implanted into mice deficient for the small Ca2+-binding protein S100A4 (S100A4−/−) was accompanied by low numbers of peripheral MDSCs. This was independent of S100A4 expression on tumor cells. In contrast, MDSCs from S100A4−/− tumor bearing mice showed a diminished resistance to the induction of intrinsic apoptosis. Further studies demonstrated that S100A4 protects MDSCs from apoptosis through Toll-like receptor-4/extracellular signal-regulated kinase-dependent caspase-9 inhibition. The finding that S100A4 is critical for MDSC survival in inflammatory environments might have important implications for the clinical treatment of cancer or inflammation-related diseases.